Integrated multi-omics analysis reveals that Gongying San ameliorates subclinical mastitis by modulating intestinal microbiota and metabolites in dairy cows - Zhao, Guoqing; Li, Hongxia; Huang, Liwei; Cheng, Yu; Liu, Jia; Song, Ruigao; Wang, Xi (Frontiers in Veterinary Science, 2025)
IntroductionSubclinical mastitis (SCM) is a common disease in dairy cows associated with dysbiosis of the gastrointestinal microbiota and systemic inflammatory response. Gongying San (GYS), a commonly used herbal formula for the treatment of mastitis, has anti-inflammatory, antibacterial and antioxidant effects, but the underlying mechanisms remain unknown. Therefore, we performed a multi-omics analysis to determine the effects of GYS on intestinal microbiota and metabolites in cows with SCM.MethodsA total of 32 Holstein cows were divided into four groups of 8 cows each, including healthy control group, subclinical mastitis group, GYS treatment group (290 g/day) and ceftiofur treatment group (2.2 mg/kg bw).ResultsGYS significantly increased milk yield, lactose and milk protein, and decreased somatic cell count (SCC) in milk from cows with SCM. In the serum, GYS decreased the levels of lipopolysaccharide (LPS), interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-8 (IL-8), interleukin-10 (IL-10), tumor necrosis factor-α (TNF-α) and malondialdehyde (MDA) and increased the concentration of superoxide dismutase (SOD). In addition, there was an increase in UCG-010 and Blautia and a decrease in Bacteroides, Lachnospiraceae, and Agathobacter in feces after GYS treatment. Fecal untargeted metabolomics showed that GYS supplementation mainly downregulated inflammation-related metabolism, including arachidonic acid and choline metabolism.DiscussionIn the treatment of SCM, GYS showed multi-target therapeutic advantages of anti-inflammatory, antioxidant and immunomodulatory properties compared to antibiotics. Bacteroides, Lachnospiraceae and UCG-010 may be involved in the regulation of inflammation through 3-oxo-Δ4bile acids and phosphatidylcholine.